PSYCHOLOGICAL AND COMPARATIVE-TYPOLOGICAL ANALYSIS IN UZBEK EPISTOLARY PROSE (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the modern stages of development of Uzbek epistolary prose using psychological and comparative-typological approaches. In particular, different forms of epistolary expression in the works of O‘tkir Hoshimov, Xurshid Do‘stmuhammad, Xayriddin Sultonov, Iqbol Mirzo, and Ilhom G‘aniyev are studied. The article explains that epistolary prose in contemporary Uzbek literature has become not only a means of communication but also an artistic system that performs deep psychological and philosophical functions. Through comparative-typological analysis, the importance of the epistolary form as a universal artistic model is revealed.
Keywords: Epistolary genre, psychologism, inner monologue, stream of consciousness, comparative-typological analysis, emotional experience